Dehydrated candied pineapple browning during stage - Mapalo, Thelma P.
the extent of browning was studied on pre-treated dehydrated candied pineapple. Steam blanching for 4 mins and sulfiting at 0.3% level proved to be the most adequate pre-treatment to prevent browning. Absorbance readings revealed that both sulfited and blanched samples had lower rates of browning compared to the control sample. Rate of browning was affected by the increase in moisture content of the control sample. Moisture content of sulfited and blanched sample also increased but at much slower rates thus the browning process was slow. it was concluded that the rate of browning was affected by the increase in moisture content of the sample during storage.